Antifungal activity and detailed chemical characterization of Cistus ladanifer phenolic extracts - Barros, Lillian (2013)
The life-threatening mycoses caused by opportunistic fungal pathogens (mainly species from the genus Candida) associated with nosocomial infections, are one of the major health problems in our days. Therefore, it is crucial to identify new compounds, especially natural ones, that are active against the most broaden spectrum of Candida species. Herein, a screening of the antifungal potential of a phenolicextract of Cistusladanifer from Northeastern Portugal, against Candida species was performed. Furthermore, the extract was characterized by HPLC–DAD-ESI/MS. Phenolic acids and derivatives (3.96 mg/g extract), ellagic acid derivatives (30.34 mg/g extract), and flavonoids (4.15 mg/g extract), such as catechins, flavonols and flavones, were found in the sample. The most abundant group was ellagic acid derivatives in which punicalagin gallate, a derivative of punicalagin attached to gallic acid, was found in highest amount (15.99 ± 0.02 mg/g extract). These compounds (i.e., ellagitannins) could be related to the strong inhibition of Candida albicans, C. glabrata and C. parapsilosis growth (MIC < 0.05 mg/mL). Moreover, the best antifungalactivity was against C. glabrata, where the studied extract was able to cause at least 3 log of reduction at concentrations below 0.05 mg/mL and a total growth inhibition at concentrations above 0.625 mg/mL.